Supercomputing and the Transformation of Science. - Kaufmann, William J. (Scientific American Library, 1993)
The O'Donnell Foundation is pleased to donate this book to all public high school and college and university libraries in California and Texas. We consider this book a classic. Supercomputing is transforming science. Computing power, along with applied mathematics and visualization technology, are our new tools to solve real problems, such as safeguarding the environment, applying genetics to cure human disease and finding sources of safe and affordable energy.